Fonte: corpo, água e luz - Peres, Carolina [UNESP] (2015)
This research arises from a reflection on a personal photography experience based on using two different cameras. The characteristics of these devices, printed on image, generated a questioning which served as motivation to deepen the theme of the photographic device and poetic of image. The research develops through theoretical and practical way, and it is in this context that takes place the creation of the photographic work Fonte. The issues related to the photographic device, analyzed from the perspective of Vilém Flusser and Gilbert Simondon, serve as a guide to reflect the creative process, to make evident elements like poetic, body relationship between photographer and camera and the construction of narratives